Dose-response relationships of resistance training in Type 2 diabetes mellitus: a meta-analysis of randomized controlled trials - Su, Wanying; Tao, Meiyi; Ma, Lin; Tang, Ke; Xiong, Fang; Dai, Xuan; Qin, Yuelan (Frontiers in Endocrinology, 2023)
Background: Globally, type 2 diabetes mellitus (T2DM) accounts for approximately 90% of diabetes cases. Resistance training (RT) is frequently employed to diminish Glycated Hemoglobin (HbA1c) and Fast Blood Glucose (FBG) levels in T2DMpatients. Yet, the specific dose-response relationships between RT variables such as training duration, frequency, and intensity for T2DM remain under-researched.Objectives: This meta-analysis aimed to elucidate the overarching effects of RT on HbA1c and FBG metrics and to provide dose-response relationships of RT variables. This was achieved by examining randomized controlled trials (RCTs) that reported reductions in HbA1c and FBG among T2DM patients.: Comprehensive literature searches were conducted up to 25 th February 2023 across databases including EMBASE, Pubmed, Cochrane, CENTRAL, Web of Science, CNKI, Wanfang Data, VIP Database for Chinese Technical Periodicals, and the Chinese Biomedical Database. The Physical Therapy Evidence Database (PEDro)was leveraged to appraise the quality of selected studies based on predefined inclusion and exclusion criteria. The meta-analysis was conducted using Stata 16.Results: 26 studies that include 1336 participants met the criteria for inclusion. RT significantly reduced HbA1c and FBG levels in comparison to control groups (P<0.05). Meta-regression analyses revealed that the number of repetitions per set (p=0.034) was a significant predictor of RT's efficacy on HbA1c. Subgroup analyses 2 indicated that the most pronounced reductions in HbA1c and FBG occurred with a training duration of 12-16 weeks, intensities of 70-80% of 1 RM, training frequencies of 2-3 times per week, 3 sets per session, 8-10 repetitions per set, and less than a 60-second rest interval.The beneficial impact of RT on HbA1c and FBG in T2DM patients is affirmed by this systematic review and meta-analysis. Moreover, the critical training parameters identified in this study are pivotal in enhancing HbA1c and FBG reductions, providing a reference for clinical staff to formulate RT exercise regiments for T2DM patients.